2012
DOI: 10.1189/jlb.0312165
|View full text |Cite
|
Sign up to set email alerts
|

BET bromodomain inhibition as a novel strategy for reactivation of HIV-1

Abstract: The persistence of latent HIV-1 remains a major challenge in therapeutic efforts to eradicate infection. We report the capacity for HIV reactivation by a selective small molecule inhibitor of BET family bromodomains, JQ1, a promising therapeutic agent with antioncogenic properties. JQ1 reactivated HIV transcription in models of latent T cell infection and latent monocyte infection. We also tested the effect of exposure to JQ1 to allow recovery of replication-competent HIV from pools of resting CD4(+) T cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
222
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(228 citation statements)
references
References 58 publications
5
222
1
Order By: Relevance
“…Brd4 binds P-TEFb through BD II, but JQ1 has a higher affinity for BD I (K d ϳ50 nM for BD I; K d ϳ90 nM for BD II). In the experiments of Banerjee and colleagues [11], experimental concentrations were 500 nM; assuming the cellular drug concentrations were in the same range, it is possible that both BD I and II were occupied by JQ1. Do both bromodomains need to be bound by drug to see the effect?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Brd4 binds P-TEFb through BD II, but JQ1 has a higher affinity for BD I (K d ϳ50 nM for BD I; K d ϳ90 nM for BD II). In the experiments of Banerjee and colleagues [11], experimental concentrations were 500 nM; assuming the cellular drug concentrations were in the same range, it is possible that both BD I and II were occupied by JQ1. Do both bromodomains need to be bound by drug to see the effect?…”
mentioning
confidence: 99%
“…In this issue of the Journal of Leukocyte Biology, Banerjee et al [11] examine the effect of a relatively new drug, JQ1, on reactivation of latent HIV-1 in cell culture systems. In contrast to other commonly used latency-reversing agents, JQ1 is not an HDAC inhibitor.…”
mentioning
confidence: 99%
“…Although JQ1 alone did not reactivate HIV from latently infected primary resting T cells because their levels of P-TEFb are vanishingly low (6,35), JQ1 could become a candidate for combinatorial anti-latency therapy with SAHA and/or other T cell-activating compounds. To this end, during the preparation of this manuscript, Montano and colleagues (36) reported that JQ1 could reactivate minimally latent HIV in , and cell lysates were subjected to immunoprecipitations (IP) with anti-CycT1 (left panels) and anti-BRD4 (right panels) antibodies. The levels of the indicated proteins in the 5% input (right panels) and immunoprecipitations (left panels) were determined by Western blotting (WB).…”
Section: Discussionmentioning
confidence: 99%
“…Newer approaches have shown an interest in a novel group of transcriptional regulators that control viral gene expression. These include the bromodomain (BET family) inhibitors that can induce the activation of latent HIV-1 in primary cell models of latency [67][68][69]. Thus, understanding the molecular underpinnings of transcriptional regulation would enhance the progress towards development of a cure for HIV infection.…”
Section: Resultsmentioning
confidence: 99%